2017
DOI: 10.1016/j.respol.2016.12.003
|View full text |Cite
|
Sign up to set email alerts
|

The importance of pro-social behaviour for the breadth and depth of knowledge transfer activities: An analysis of Italian academic scientists

Abstract: shown that academics are essentially motivated by learning opportunities, fundraising and satisfaction derived from puzzle solving in research activities, our paper provides evidence of the positive role of an additional motivation for both the breadth and depth of KT: the extent to which the academic scientist advances the societal role of universities ("mission" motivation). We find that both "funding" and "mission" motivations have a positive effect on the variety and intensity of KT activities, with little… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
82
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(99 citation statements)
references
References 83 publications
3
82
0
3
Order By: Relevance
“…Although since then the number of studies addressing individual interaction has increased significantly, as shown in Perkmann et al (2013), most contributions have focused on personal characteristics such as sex, age, seniority, and academic standing of the scholar as drivers of academic entrepreneurship. However, less emphasis has been given to proximities, particularly those that differ from spatial ones, and to sociological aspects, such as social ties and the prosocial attitude of researchers, up until very recently (Iorio et al 2017).…”
Section: Individual Characteristics Proximities and Academic Engagementmentioning
confidence: 99%
“…Although since then the number of studies addressing individual interaction has increased significantly, as shown in Perkmann et al (2013), most contributions have focused on personal characteristics such as sex, age, seniority, and academic standing of the scholar as drivers of academic entrepreneurship. However, less emphasis has been given to proximities, particularly those that differ from spatial ones, and to sociological aspects, such as social ties and the prosocial attitude of researchers, up until very recently (Iorio et al 2017).…”
Section: Individual Characteristics Proximities and Academic Engagementmentioning
confidence: 99%
“…Además, se necesitan diseñar estructuras de estímulos para motivar a los investigadores en la creación de nuevo conocimiento y vincularse en la implementación del proceso. Los estímulos pueden ser de tipo financiero, pero también social, puesto que muchos investigadores desean contribuir con la solución de problemáticas sociales mediante su trabajo (Lorio, Labory y Rentocchini, 2017). Asimismo, existe el desafío de eliminar las barreras de egoísmo entre los investigadores y propiciar un ambiente donde el conocimiento y experiencia se transfiera de forma natural (Cheng, et al, 2009).…”
Section: Desafíos De La Gestión Del Conocimiento En Instituciones De unclassified
“…Furthermore, it provides access to the diverse knowledge base of industry practitioners (D'Este and Patel, 2007;Iorio et al, 2017). Yet, a broad KT portfolio requires internal processes and infrastructure to support the different KT activities (Guerrero and Urbano, 2012).…”
Section: The Diversity and Intensity Of Knowledge-transfer Activitiesmentioning
confidence: 99%